Cross-Linguistic Transfer in Law Students’ Writing in a Basic English Course - Komang Agus Ariawan; Ni Luh Putu Sri Adnyani; I Made Suta Paramarta (MAN 4 Kota Pekanbaru, 2026)
This study investigated cross-linguistic transfer in the English writing of first-semester law students enrolled in a Basic English course. It aimed to identify the types of cross-linguistic transfer and examine how Indonesian morphological and syntactic features influenced students’ written production. A descriptive qualitative design was employed, using qualitative content analysis to analyze 30 students’ written texts. The findings revealed that negative transfer was more prevalent than positive transfer, accounting for 247 (73.51%) and 89 (26.49%) unique instances, respectively. At the morphological level, affixation and derivation emerged as the most dominant feature, whereas clause construction was the most frequent syntactic feature. These findings indicate that structural differences between Indonesian and English substantially influenced students’ grammatical accuracy. The study contributes to a better understanding of cross-linguistic transfer in an English for Specific Purposes (ESP) context and provides pedagogical insights for improving English writing instruction.